2016
DOI: 10.1136/bmjopen-2016-011100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal pain of the neck, upper extremities and lower back among dental practitioners working in Riyadh, Saudi Arabia: a cross-sectional study

Abstract: ObjectivesStudies have shown that dentists have a higher incidence of work-related musculoskeletal (MSK) pain than those in other occupations. The risk factors contributing to MSK pain among Saudi dentists has not been fully studied so this study aims to estimate the prevalence of MSK pain and investigate its associated risk factors among dentists in Saudi Arabia.Setting and participantsA cross-sectional survey was carried out in the capital city Riyadh, Saudi Arabia, using random cluster sampling. 224 surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
119
5
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(147 citation statements)
references
References 32 publications
13
119
5
6
Order By: Relevance
“…Pain in the lower back, as shown in this study was significantly more prevalent than in any other parts of the axial region, and this finding was consistent with Dantas et al In addition, this finding was consistent with many other studies [13,14]. The main risk factor for lower back pain associated with dental work is the poor and unsupported sitting position.…”
Section: Advances In Health Sciences Research Volume 4 4 Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Pain in the lower back, as shown in this study was significantly more prevalent than in any other parts of the axial region, and this finding was consistent with Dantas et al In addition, this finding was consistent with many other studies [13,14]. The main risk factor for lower back pain associated with dental work is the poor and unsupported sitting position.…”
Section: Advances In Health Sciences Research Volume 4 4 Discussionsupporting
confidence: 93%
“…Musculoskeletal disorders in dentists have been the subject of numerous studies worldwide, and the overall prevalence of musculoskeletal disorders in dentists ranges from 66 to 93 percent [7][8][9][10]. Various studies have shown that when MSD is found in dentists, it is located in specific regions such as the neck [5,10,11] and the lower back [12][13][14]. The purpose of this study is to describe the most common types and locations of MSD in dentists working at the Public Healthcare Center in Bandung City.…”
Section: Introductionmentioning
confidence: 99%
“…The studies that fulfilled the criteria for reporting prevalence were the same studies deemed to have a low risk of bias. Five studies [12][13][14][15] met the inclusion criteria and these studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Un estudio en Portoviejo (Ecuador) en el 2012 arrojó una prevalencia del dolor en odontólogos del 74% (11). Al-Mohrej et al en un estudio en el año 2016 en odontólogos de Arabia Saudita reportaron que el 90,2% tuvo dolor musculoesquelético (12). Alexopoulos determinó una prevalencia del 62% en odontólogos griegos (13).…”
Section: Discussionunclassified